(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Implant therapy is currently considered to be a successful and acceptable means to restore missing teeth.1 It is essential for long-term success of any implant prosthesis to achieve a passive fit between the fixture and the superstructure.4 Minimizing the misfit to prevent possible complications is a generally accepted goal of prosthodontic implant procedure. Since the accuracy of the impression affects the accuracy of the definitive cast, an accurate impression is essential to fabricate a prosthesis with good fit.